All‐oral therapy with nucleotide inhibitors sofosbuvir and GS‐0938 for 14 days in treatment‐naive genotype 1 hepatitis C (NUCLEAR). Issue 10 (31st March 2013) - Lawitz, E. J.; Rodriguez‐Torres, M.; Denning, J.; Mathias, A.; Mo, H.; Gao, B.; Cornpropst, M. T.; Berrey, M. M.; Symonds, W. T.
Summary: Sofosbuvir and GS‐0938 are distinct nucleotide analogues with activity against hepatitis C virus (HCV) in vitro . We evaluated the antiviral activity and safety of sofosbuvir and GS‐0938 alone and in combination in HCV genotype 1 patients. In this double‐blind study, 40 treatment‐naïve patients were randomly assigned to 4 treatment cohorts: (i) GS‐0938 for 14 days, (ii) GS‐0938 for 7 days followed by GS‐0938 plus sofosbuvir for 7 days, (iii) sofosbuvir for 7 days followed by GS‐0938 plus sofosbuvir for 7 days and (iv) GS‐0938 plus sofosbuvir for 14 days. In each arm, 8 patients received active drug and 2 placebo. After 7 days of dosing, patients in all 4 dose groups experienced substantial reductions in HCV RNA, with median declines (Q1, Q3) of −4.50 (−4.66, −4.24) in Cohort 1, −4.55 (−4.97, −4.13) in Cohort 2, −4.65 (−4.78, −4.17) in Cohort 3 and −4.43 (−4.81, −4.13) in Cohort 4; patients receiving placebo had essentially no change in HCV RNA (+0.07 log10 IU/mL). Seven days after the end of treatment, the proportions of patients with HCV RNA <15 IU/mL were 4 (50%), 8 (100%), 7 (88%) and 5 (63%) for Cohorts 1–4, respectively, vs 0 for placebo. No viral breakthrough or resistance mutations were observed. No serious adverse events or Grade 3 or 4 adverse events were reported. Sofosbuvir and GS‐0938—alone and in combination—were well tolerated and led to substantial reductions in viral load. Sofosbuvir is undergoing further investigation as a possible backbone of an all‐oral regimen for chronic HCV.